THE INVESTIGATION OF CEPHEIDS RT AUR, T VUL, κ PAV BY A TWO-COMPONENT - Fenina, Z. N.; Zgonyaiko, N. S.; Vasilyeva, S. V. (Одеські астрономічні публікації, 2017)
For 3 cepheids (RT Aur, T Vul, κ Pav) the physical and chemical parameters are obtained: spectral class, electron pressure, "microturbulent velocity", relative number of atoms in different chemical elements. The variations of this parameters with a phase are investigated.